2020
DOI: 10.1371/journal.pone.0232936
|View full text |Cite
|
Sign up to set email alerts
|

Museomics for reconstructing historical floristic exchanges: Divergence of stone oaks across Wallacea

Abstract: Bagui monophyletic, raising the possibility of multiple independent dispersals along the outer edge of Wallacea. This suggests that dispersal of large seeded tree genera throughout Malesia and across Wallacea may have been less affected by large geographic distances and the presence of marine barriers than generally assumed. We demonstrate the utility of MIGseq in museomic studies using non-model taxa, presenting the first range-wide genomic assessment of Lithocarpus and tropical Fagaceae as a proof-of-concept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 89 publications
0
13
0
Order By: Relevance
“…Incorporating new techniques [ e.g. , MIG-seq ( Suyama and Matsuki 2015 ); high-throughput sequencing of target-enriched libraries ( Jones and Good 2016 ; Bossert and Danforth 2018 ; Johnson et al 2019 )] could provide valuable data from rare or unplaced ( Binh et al 2018 ), extinct ( Feigin et al 2018 ), or herbarium specimens ( Strijk et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Incorporating new techniques [ e.g. , MIG-seq ( Suyama and Matsuki 2015 ); high-throughput sequencing of target-enriched libraries ( Jones and Good 2016 ; Bossert and Danforth 2018 ; Johnson et al 2019 )] could provide valuable data from rare or unplaced ( Binh et al 2018 ), extinct ( Feigin et al 2018 ), or herbarium specimens ( Strijk et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Other recent studies using MIG-seq on Hosta (Yahara et al 2021a) and Stellaria (Yahara et al 2021b) have also demonstrated its usefulness in resolving taxonomic complexity and describing new taxa. As this method is more applicable to a small number of poor-quality samples than RAD-seq (Binh et al 2018;Strijk et al 2020;Zhang et al 2020), it is expected to be used for taxonomic studies of many groups for which reliable phylogenetic relationships could not be reconstructed by conventional molecular phylogenetic methods. Japanese name.…”
Section: Discussionmentioning
confidence: 99%
“…MIG-seq is a polymerase chain reaction (PCR)-based next-generation sequencing (NGS) method, which has been recently developed as an effective method for the discovery of genome-wide SNPs from low-quantity or low-quality DNA (Suyama and Matsuki, 2015). It has been used successfully and effectively to clarify persistent taxonomic difficulties or issues for several plant groups with complex evolutionary history based on genome-wide SNPs (Binh et al, 2018;Gutiérrez-Ortega et al, 2018;Yoichi et al, 2018;Park et al, 2019Park et al, , 2020Takata et al, 2019;Strijk et al, 2020;Nakamura et al, 2021;Onosato et al, 2021). In addition to determining the interspecific relationships based on the genome-wide SNPs, we compared the genetic diversity and population genetic structure between the insular derivative, P. takesimensis, and the purported continental ancestor, P. sargentii, using chloroplast DNA (cpDNA) as a maternally inherited marker.…”
Section: Introductionmentioning
confidence: 99%